The principle of economics in the procedure of deprivation of parental rights - Đerlek Minela (Trendovi u Poslovanju)
Deprivation of parental rights is one of the most difficult forms of state interference and intervention in family legal relations. It appears and is represented today as one of the current topics of this institute. From complete authority over the child, we have come to the path of the child as the holder of rights, the child as an important link in the entire society. The state derives the legitimacy of participation in this new position of the child, where it appears as its complete and ultimate protector against parents who do not perform their duty adequately. But is it always like that? Is it in the interest of the child and when? These are the questions we will try to answer with a comparative legal, methodological and historical analysis of this institute. The aim of this paper is to highlight the degree of importance of the child's interests when making a decision on deprivation of parental rights.